Bimodal Distributions in the Space of a Non-Uniform Weight - Lemesheva, N.V. (Журнал математической физики, анализа, геометрии, 2015)
Bimodal approximate solutions of the Boltzmann equation for the model of hard spheres, which describe the interaction between the "acceleration- packing" °ows, are constructed. Some sufficient conditions for infinites- imalityof the mixed error "with weight" between the left-hand and the right-hand sides of the equation are obtained. Построены бимодальные приближенные решения уравнения Больцмана для модели твердых сфер, которые описывают взаимодействие между потоками типа "ускорение-уплотнение". Найдены некоторые достаточные условия для минимизации смешанной невязки "с весом" между частями этого уравнения.